INVERSE PROBLEM OF THE STURM-LIOUVILLE OPERATOR WITH UNSEPARATED BOUNDARY VALUE CONDITIONS AND SYMMETRIC POTENTIAL - A.Sh.Shaldanbayev; A.A.Shaldanbayeva; B.A.Shaldanbay (Academic Scientific Journal of Computer Science, 2019)
In the paper we prove the uniqueness theorem on a single spectrum for the Sturm-Liouville operator with unseparated boundary value conditions and real continuous symmetric potential. The research method is different from all known methods, and is based on the internal symmetry of the operator generated by invariant subspaces.